Manajemen Humas untuk Meningkatkan Animo Masyarakat terhadap Pesantren Modern Ummul Qura Kabupaten Bireuen - Annabila, Cut Ila; Yusrianti, Susi; Barus, Jumat (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2024)
This study aims to deeply understand the role of optimizing PR management in building public interest in Ummul Qura Modern Islamic Boarding School in Bireuen Regency. Using a qualitative approach and descriptive method, this study involved informants selected by purposive sampling, including principals, teachers, and PR staff, who have knowledge and experience related to PR program management in pesantren. Data were collected through semi-structured interviews, participant observation, and documentation studies, which were then thematically analysed to find relevant patterns. The results showed that the optimization of PR management at Ummul Qura Modern Islamic Boarding School succeeded in increasing public interest through the implementation of effective communication strategies and the use of digital media. The active involvement of the community in pesantren activities, as well as data-based evaluation of PR programs, also contribute to the positive image of the institution. The increase in the number of students from 180 to 222 in the last two years is an indicator of the success of the strategy implemented. Based on these findings, this study recommends that Ummul Qura Modern Pesantren continue to develop training for PR staff in the use of technology and digital media. In addition, it is important to strengthen community involvement in social activities and implement continuous evaluation to improve the effectiveness of PR programs. Thus, the pesantren can continue to adapt to local needs and strengthen its position as a relevant and responsive educational institution in the modern era.